Pengaruh Permainan MONAGEN (Monopoli Tenaga Eksogen) Terhadap Minat Belajar Siswa Kelas X IPS SMAN 12 Jakarta - Aldiansyah, Iqbal; Aris Munandar; Rayuna Handawati (JPUS: Jurnal Pendidikan Untuk Semua, 2025)
This research aims to find out the influence of MONAGEN games on students' learning interest class X IPS SMAN 12 Jakarta. This research uses quasi-experimental research methods with the Nonequivalent Control Group Design design. The sampling techniques in this study used Purposive Sampling. The samples used in this study, namely class X IPS 3 as an experimental class given MONAGEN game treatment and class X IPS 1 as a control class given PowerPoint treatment. These research instruments include: student learning interest instruments (Pre-Test & Post-Test), MONAGEN game (X), and observation sheets of student learning interest. Analytical techniques used in this research, namely instrument tests, tests as data analysis requirements, and data analysis tests. Research instruments are declared valid and realable, and the data is declared normal and homogeneous. Based on the results of the study showed that there was a significant influence of MONAGEN games on students' learning interests in class X IPS SMAN 12 Jakarta. The average post-test acquisition of experimental classes was 82% by category " Excellent " and the control class by 76% by category " Very Good ". Analysis of the data using the Independent Sample T-Test test obtained that the significance level (Sig.) of 0.025 due to significance smaller than 0.05 (0.025 < 0.05), then Ho was rejected and Ha was accepted. The influence of student interest in learning "Very Good" in class X IPS SMAN 12 Jakarta after using the MONAGEN game in geography learning.